Improving food quality with novel food processing technologies - Tokuşoğlu, Özlem, 1970-; Swanson, Barry Grant, 1944- (CRC Press, 2014)
"Improving food quality, specifically properties such as rheological, physicochemical, and sensorial aspects, is always a goal of food and beverage manufacturers. During the past decade, novel processing technologies including high hydrostatic pressure (HHP), ultrasound, pulse electric field (PEF), and advanced heating technologies containing microwave, ohmic heating, and radio frequency have frequently been applied in the processing of foods and beverages. This book addresses maintaining and improving food quality through the use of these novel food processing technologies"--Resumé vydavatele
Keywords: potravinářská technologie; výroba potravin; kvalita potravin; food technology; food production; food quality; kolektivní monografie; collective monographs